A Case of Biphasic Pulmonary Blastoma Treated with Carboplatin and Paclitaxel plus Bevacizumab. (13th May 2015) - Sakata, Shinya; Saeki, Sho; Hirooka, Sayuri; Hirosako, Susumu; Ichiyasu, Hidenori; Kohrogi, Hirotsugu
Abstract : Background . Pulmonary blastoma is a rare lung tumor similar to fetal lung tissues. Surgical resection at early stage is more curative than other treatments, but there is no standard treatment in unresectable cases. We show a case treated with carboplatin and paclitaxel plus bevacizumab. Case . A 68-year-old man received surgical resection and was diagnosed with biphasic pulmonary blastoma (pT3N0M0 stage IIB). Metastasis to the spleen was detected six weeks after the surgery. Carboplatin, paclitaxel, and bevacizumab were administered and showed an effect on the metastasis. Four courses of the chemotherapy were completed, but a metastasis was found and the metastatic tumor in the spleen was enlarged. After that, chemotherapy was not effective afterward and he died of the progression of biphasic pulmonary blastoma on the 292nd day of illness. Conclusion . In this case, chemotherapy with carboplatin and paclitaxel plus bevacizumab was temporarily efficacious for biphasic pulmonary blastoma.